Optimization of the formation of coatings based on SiAlOC glasses via structural, microstructural and electrochemical studies. (20th June 2019) - Bik, M.; Szewczyk, J.; Jeleń, P.; Długoń, E.; Simka, W.; Sowa, M.; Tyczkowski, J.; Balcerzak, J.; Bik, E.; Mroczka, K.; Leśniak, M.; Barańska, M.; et al.
Abstract: The main objective of this work was to determine the tightness and wet corrosion resistance of SiAlOC glasses in the form of coatings on a steel substrate. The coatings were optimized in terms of the formation process, along with their resulting structure and microstructure. The coating material was obtained using sol-gel-synthesized, Al-doped, ladder-like polysilsesquioxanes as glasses' precursors. The layers were deposited by means of the dip-coating technique, for which the influence of both surface preparation (grinding/polishing) and withdrawal speed (5, 15, and 30 cm/min) was investigated. After the deposition, a two-stage thermal treatment (curing −70 °C/air and pyrolysis −800 °C/Ar) was applied. A series of structural (XRD, XPS, Raman) studies confirmed the formation of SiAlOC glass coatings, with a noticeable presence of an additional inner layer, most probably of MnCr2 O4 spinel. Furthermore, the direct correlation between the increasing content of aluminum and the decreasing amount of carbon inward the coating can be suggested. Additionally, spectroscopic studies revealed the ongoing amorphization process of the free carbon phase. The result was that more crystalline species were present at the surface of the coating and the amorphous phases were near the inner MnCr spinel layer. Moreover, a set of microstructural (SEM, EDS, Confocal) studies was performed to evaluate the influence of the investigated deposition parameters on the coatings' compactness, homogeneity, and thickness. The coating with the best characteristics obtained on the ground substrate when using the lowest withdrawal speed was chosen for the final examination of the tightness via electrochemical corrosion studies in a wet environment of chloride ions. The wet corrosion resistance was nearly 60 times higher for the coated specimen in comparison with the bare steel substrate. Additionally, an uncoated specimen after the same thermal treatment was investigated with the use of the same electrochemical studies. It exhibited significantly higher resistance to the corrosion in the wet environment than the rest of the samples due to the pre-formation of a mixed scale containing highly resistant Cr2 O3 .